Vanishing Lung Syndrome in a Patient with HIV Infection and Heavy Marijuana Use. (8th January 2014) - Tashtoush, Basheer; Gonzalez-Ibarra, Fernando; Memarpour, Roya; Hadeh, Anas; Smolley, Laurence
Abstract : Vanishing lung syndrome (VLS) is a rare and distinct clinical syndrome that usually affects young men. VLS leads to severe progressive dyspnea and is characterized by extensive, asymmetric, peripheral, and predominantly upper lobe giant lung bullae. Case reports have suggested an additive role of marijuana use in the development of this disease in young male tobacco smokers. We herein report a case of a 65-year-old Hispanic male previously diagnosed with severe emphysema and acquired immune deficiency syndrome (AIDS), with a history of intravenous heroin use and active marijuana smoking who presents to the emergency department with severe progressive shortness of breath he was found to have multiple large subpleural bullae occupying more than one-third of the hemithorax on chest computerized tomography (CT), characteristic of vanishing lung syndrome. The patient was mechanically ventilated and later developed a pneumothorax requiring chest tube placement and referral for surgical bullectomy. Surgical bullectomy has shown high success rates in alleviating the debilitating symptoms and preventing the life threatening complications of this rare syndrome. This case further emphasizes the importance of recognizing VLS in patients with severe emphysema and heavy marijuana smoking.